2021
DOI: 10.1016/j.sjbs.2021.06.010
|View full text |Cite
|
Sign up to set email alerts
|

Inorganic polyphosphate from the immunobiotic Lactobacillus rhamnosus CRL1505 prevents inflammatory response in the respiratory tract

Abstract: Lactobacillus (L.) rhamnosus CRL1505 accumulates inorganic polyphosphate (polyP) in its cytoplasm in response to environmental stress. The aim of this study was to evaluate the potential effects of polyP from the immunobiotic CRL1505 on an acute respiratory inflammation murine animal model induced by lipopolysaccharide (LPS). First, the presence of polyP granules in the cytoplasm of CRL1505 strain was evidenced by specific staining. Then, it was demonstrated in the intracellular extracts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“…The study of poly-P production in lactobacilli, bifidobacteria and probiotics in general received low attention until this molecule was reported as a functional bacterial metabolite 10 . Since then, probiotic-derived poly-P has been characterized as a beneficial molecule that protects against intestinal injury 7 , 9 , but additional functions in preventing inflammatory processes at different locations are also being reported 39 , 40 . In this study, we show that, under the tested conditions with our collection of probiotics, production of poly-P was highly variable among strains.…”
Section: Discussionmentioning
confidence: 99%
“…The study of poly-P production in lactobacilli, bifidobacteria and probiotics in general received low attention until this molecule was reported as a functional bacterial metabolite 10 . Since then, probiotic-derived poly-P has been characterized as a beneficial molecule that protects against intestinal injury 7 , 9 , but additional functions in preventing inflammatory processes at different locations are also being reported 39 , 40 . In this study, we show that, under the tested conditions with our collection of probiotics, production of poly-P was highly variable among strains.…”
Section: Discussionmentioning
confidence: 99%
“…Previous results revealed that Lr-CRL1505 has multiple functions, for instance, as a probiotic can enhance immune responses in the gut (Salva et al 2010 ) and provide protection against bacterial respiratory pathogens, respiratory syncytial virus, and influenza virus (Zelaya et al 2015 , 2016 ; Tonetti 2020 ). Furthermore, its intracellular extract with polyP (as a postbiotic) was able to prevent the development of local inflammatory response in the respiratory mucosa in a murine model of acute respiratory inflammation (Correa Deza et al 2021a ), a fact that allows new applications of Lr-CRL1505 as a probiotic and postbiotic. In this work, the effect of culture parameters (pilot scale biomass production, pH and growth phase) on cell viability, heat tolerance and polyP accumulation by Lr-CRL1505 was evaluated in order to establish better conditions to obtain, on the one hand, heat-tolerant biomass with a high percentage of live cells and, on the other hand, intracellular extracts with high polyP levels, depending on the destination of the functional product (probiotic or postbiotic).…”
Section: Discussionmentioning
confidence: 99%
“…S1). By DAPI-based fluorescence technique, there is a threshold below which short polyP chains are not detectable, however, the polyP chain length from Lr-CRL1505 was previously reported greater than 45 phosphate residues (Correa Deza et al 2021a ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequent research has revealed that poly-P derived from probiotics offers several benefits, such as protecting against intestinal injury (Kashima et al 2015, Fujiya et al 2020. Additionally, there are emerging reports suggesting its role in preventing inflammatory processes at various locations (Deza et al 2021, Takauji et al 2021. While poly-P is not actively transported, trace levels can be detected outside the cells (Saiki et al 2016).…”
Section: Ache/bche Activity Determination and Inhibition Studiesmentioning
confidence: 99%